Peru LNG : A Focus on Continuous Improvement - International Finance Corporation (World Bank, Washington, DC, 2014)
Extractive industry companies, particularly those operating in areas of high biodiversity value, on indigenous lands, or in close proximity to communities, face operational and reputational risks related to their environmental and social performance, and can be subject to intense scrutiny from stakeholders. PERU Liquefied Natural Gas (PLNG), the first liquefied natural gas plant in South America, is an example of a high-profile project facing multiple environmental and social risks. Launched in 2007, the $3.8 billion project is one of the largest industrial projects in Peru. PLNG is considered one of Peru's key resources, and it is a core component of the Peruvian government's energy strategy. Over the course of six years, PLNG has shown a strong commitment to managing environmental and social risks throughout all the phases of the project. The project is currently in the operations and maintenance phase, having completed construction in 2010. Liquefied natural gas pipeline projects are often associated with a number of environmental and social risks that must be addressed by a comprehensive risk management system. Some of the issues faced by the PLNG project included: 1) several communities and other stakeholders living in or using the project footprint; 2) health and safety risks due to hiring large numbers of new workers; 2) potential for safety incidents and accidents from vehicle use; 3) the presence of ecologically sensitive areas, particularly the Andean wetlands; and 5) the presence of 35 rural Andean communities along the pipeline. This lessons of experience publication documents experience and lessons learned throughout the lifecycle of the project that are transferable to other projects.